2017
DOI: 10.1016/j.scitotenv.2016.11.103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the addition of nitrogen and sulfate on CH4 and CO2 emissions, soil, and pore water chemistry in a high marsh of the Min River estuary in southeastern China

Abstract: Exogenous nitrogen (N) and sulfate (SO), resulting from human activity, can strongly influence the emission of CH and CO from soil ecosystems. Studies have reported the effects of N and SO on CH and CO emissions from inland peatlands and paddies. However, very few studies have presented year-round data on the effects of the addition of N and SO on CH and CO emissions in estuarine marshes. The effects of the addition of N and SO on the emission of CH and CO were investigated in a Cyperus malaccensis marsh in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 62 publications
3
9
0
Order By: Relevance
“…A number of studies have reported significant effects of soil temperature, soil moisture, and fertilizer application on CO 2 fluxes (Abagandura, Şentürklü, et al, 2019; Davidson et al, 1998; Mbonimpa et al, 2015; Schaufler et al, 2010; Soosaar et al, 2011). Similar to our results, application of N and S increased CO 2 emissions in a study by Hu et al (2017), which might be due to increased root respiration with the application of exogenous nutrients.…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies have reported significant effects of soil temperature, soil moisture, and fertilizer application on CO 2 fluxes (Abagandura, Şentürklü, et al, 2019; Davidson et al, 1998; Mbonimpa et al, 2015; Schaufler et al, 2010; Soosaar et al, 2011). Similar to our results, application of N and S increased CO 2 emissions in a study by Hu et al (2017), which might be due to increased root respiration with the application of exogenous nutrients.…”
Section: Discussionsupporting
confidence: 92%
“…This discrepancy may be due to a higher N enrichment in Chinese coastal areas. The intensity of N deposition has continued to increase in China, especially in the southeastern coastal areas, and has been accompanied by very high N inputs from upstream runoff and tides (Hu et al 2017). Elevated N levels can regulate the biogeochemical processing of soil nutrients (Zhang et al 2016), promote plant growth (Högberg et al 2017), accelerate the decomposition of litter (Wang and Moore 2014), and ultimately affect plant nutrient dynamics.…”
Section: Patterns Of N and P Concentrations And N:p Ratios In China'smentioning
confidence: 99%
“…Higher CH 4 effluxes were found during the air-exposed periods in the high-tide season compared with the low-tide season (Figure 5a,b), with there being many possible explanations for this. Most importantly, the results of previous studies suggest that CH 4 effluxes are sensitive to temperature and plant growth characteristics (e.g., biomasses, primary productivities, and root exudes) [22,23,24,25], and that higher temperatures may stimulate relatively higher methanogenic activity in sediments during high-tide seasons compared with low-tide seasons [19,42,43]. In addition, as the plant biomass was more abundant in the high-tide seasons than the low-tide seasons (Table 1), this may provide more carbon-rich substrate to the methanogens [8,44].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, during the winter and early spring, the tide height is much lower, the inundation period is significantly shorter, and the tide at times does not even reach the middle or upper regions of the tidal flats [22]. Previous studies have suggested that seasonal dynamics were apparent in the CH 4 effluxes in the tidal wetlands of the Min River Estuary in the East China Sea, and that the highest CH 4 effluxes occurred during the summer months (June to August) [22,23,24,25]. However, none of these investigated the influence of tidal activities on the dynamics of CH 4 effluxes.…”
Section: Introductionmentioning
confidence: 99%